If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 7(x + 5) = 3x + 12 Reorder the terms: 7(5 + x) = 3x + 12 (5 * 7 + x * 7) = 3x + 12 (35 + 7x) = 3x + 12 Reorder the terms: 35 + 7x = 12 + 3x Solving 35 + 7x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 35 + 7x + -3x = 12 + 3x + -3x Combine like terms: 7x + -3x = 4x 35 + 4x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 35 + 4x = 12 + 0 35 + 4x = 12 Add '-35' to each side of the equation. 35 + -35 + 4x = 12 + -35 Combine like terms: 35 + -35 = 0 0 + 4x = 12 + -35 4x = 12 + -35 Combine like terms: 12 + -35 = -23 4x = -23 Divide each side by '4'. x = -5.75 Simplifying x = -5.75

| 73=54*n | | 54=73*n | | 12(x-3)=10x-13 | | -4=-2(x-4) | | 15x-1=8-3x | | 4.35p+13.7=5.6 | | 25t^2-25t-300=0 | | 8x+3=15x-5 | | 3(x-7)+25=x+9 | | -2(x-1)=-4 | | 9x-14=7x+20 | | 10x+6=8x-(-4) | | 3x+2=2(x-4) | | 3-4x=2(x-4) | | 10x+4=2x+20 | | 4(3-n)=3(n+2) | | 6=1-2 | | 8a-10-5a=20 | | 2(2k+1)=2(k-3) | | 9y-8=8y-7 | | 6z+10=34 | | 4(p-7)=3 | | 5(b+10)=2(2b-22) | | 5y-1.4=6 | | x-4.5=11.7 | | -(x+1)=5 | | 2.7-1.8y=4.5 | | 14-c/4=9 | | -3(4y-3)+4(6y+1)=43 | | 24x-16=19x | | 3(4d-20)=6(2d-10) | | x^2-16x=64 | | 1e/2+3-1e/4=8 | | 7f-20=3f-20 | | y=3y^2-4 | | -3.3x+9.3=-6.8+12.7x | | 4x+1=8x-7 | | 4(g-15)=2(g+30) | | 0=5(x+7) | | 7m+1=3m+2 | | 2y=5y^2-7 | | 5(2h+30)=10(h-15) | | -9y=2y^2+4 | | 3x+6=4x-4 | | 3i/4+8=1i/2 | | 7-8x=155-36x | | y+3+2y=-6 | | -4y=5y^2-1 | | 63-2x=25x+24 | | 6y=4y^2-4 | | 10j-4-15j=56 | | 9-9x=89-23x | | 34(a+9a)=55a-7 | | 3(k-10)=5(k+30) | | 8x-9=5x+6 | | 42-5x+13x=20 | | 16x-x^2=64 | | 63-3x=9x+18 | | 15-2m=61 | | (x-x^2)x=4 | | 4x+40=18x-68 | | 2(5-3x)+3x=14 | | 3x-9(2x+4)=3-8(2-4x) | | 4x-5=11x-64 | | -20b^8=2b^8 |